The Scott Polar Research Institute, 1920–70 - Robin, G. de Q. (Polar Record, 1971)
By a Grace, dated 26 November 1920, the Senate of the University of Cambridge approved an earlier recommendation of the Council of the Senate “That the University would welcome the establishment of the proposed Polar Research Institute at Cambridge.…” Frank Debenham's “Retrospect”, written to mark the twenty-fifth anniversary of this date, told of the circumstances that led to the formation of the Institute, and of its aims and facilities. Now, to mark the fiftieth anniversary of that date, a brief note seems appropriate.